2015
DOI: 10.1037/neu0000185
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive factors contributing to spelling performance in children with prenatal alcohol exposure.

Abstract: Objective Heavy prenatal alcohol exposure is associated with impaired school functioning. Spelling performance has not been comprehensively evaluated. We examined whether children with heavy prenatal alcohol exposure demonstrate deficits in spelling and related abilities, including reading, and tested whether there are unique underlying mechanisms for observed deficits in this population. Method Ninety-six school-age children comprised two groups: children with heavy prenatal alcohol exposure (AE, n=49) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 89 publications
(146 reference statements)
1
17
0
1
Order By: Relevance
“…Our results are consistent with previous literature which found that school-age children who have been prenatally exposed to alcohol perform significantly lower than typically developing peers across academic domains (Streissguth et al, 1990, Howell et al, 2006, O’Leary et al, 2013, Glass et al, 2015, Crocker et al, 2015). Children with prenatal exposure to alcohol demonstrated impairments on higher order mathematical reasoning as well as lower order functions such as basic numerical processing, basic calculations, proximity judgment, and cognitive estimation (Coles et al, 2009, Lebel et al, 2010, Crocker et al, 2015, Kopera-Frye et al, 1996, Meintjes et al, 2010; Jacboson et al, 2011).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our results are consistent with previous literature which found that school-age children who have been prenatally exposed to alcohol perform significantly lower than typically developing peers across academic domains (Streissguth et al, 1990, Howell et al, 2006, O’Leary et al, 2013, Glass et al, 2015, Crocker et al, 2015). Children with prenatal exposure to alcohol demonstrated impairments on higher order mathematical reasoning as well as lower order functions such as basic numerical processing, basic calculations, proximity judgment, and cognitive estimation (Coles et al, 2009, Lebel et al, 2010, Crocker et al, 2015, Kopera-Frye et al, 1996, Meintjes et al, 2010; Jacboson et al, 2011).…”
Section: Discussionsupporting
confidence: 93%
“…We found that alcohol-exposed children performed significantly worse than their demographically matched peers on spelling and reading tests, even after accounting for socioeconomic status and age. Prior research has found that alcohol-exposed children are impaired compared to controls on various aspects of verbal academic functioning (O’Leary et al, 2013, Streissguth et al, 1994a, Rose-Jacobs et al, 2012, Glass et al, 2015), however most studies, including ours, utilize fairly simple tasks such as single word oral word reading or basic spelling. Potentially, alcohol-exposed children may struggle more on complex or cognitively demanding tests of reading reasoning or comprehension and would show levels of impairment more similar to those observed on the more complex math measures.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Interventions targeting mathematical skills in children with FASD have been effective in improving some of these academic challenges (Coles et al., ). In addition to mathematical impairments, lower performance on spelling and reading is found in association with FASD (Glass et al., , ; Jirikowic et al., ). These impairments are thought to be related to deficits in working memory (Glass et al., ).…”
Section: Cognitive and Behavioral Functioningmentioning
confidence: 99%
“…Learning deficits are also apparent in the presence of decreased academic performance across domains, with particular weaknesses seen in areas of mathematical functioning (Glass, Graham, Akshoomoff, & Mattson, 2015; Goldschmidt, Richardson, Stoffer, Geva, & Day, 1996; Howell et al, 2006). Memory deficits are also seen across domains (verbal, visual, auditory), and often appear to be associated with initial encoding difficulties with relatively spared retention (Kaemingk, Mulvaney, & Halverson, 2003; Willoughby et al, 2008).…”
Section: Review Of Fetal Alcohol Spectrum Disordersmentioning
confidence: 99%